Growth promotion of Euglena gracilis by ferulic acid from rice bran - Jiangyu Zhu; Minato Wakisaka (AMB Express, 2018)
Abstract A significant growth promotion of Euglena gracilis was achieved by simply adding ferulic acid from rice bran without diminishing the accumulation of valuable products like paramylon. E. gracilis is a freshwater microalga that is widely applied in cosmetics, food, medicine, and supplements, and it is considered a potential source of biofuel. It is therefore important to enhance its yield at a lower cost for its commercial viability. Introducing a growth regulator derived from agro waste is considered a cheaper and safer strategy to improve biomass productivity compared with other alternatives such as implementing genetic engineering or adding nutrients and plant hormones as growth stimulator. The effect of ferulic acid derived from rice bran on the growth and metabolism of E. gracilis was investigated in this study. To aid in the dissolution of ferulic acid, 1% dimethyl sulfoxide (DMSO) was added to Cramer–Myers medium. Ferulic acid could alleviate the inhibitory effect of DMSO and significantly promoted the growth of E. gracilis. It was found that cell density was 2.5 times greater than that of the control group and 3.6 times greater than that of the negative control group when 500 mg/L of ferulic acid was added. In addition, the photosynthetic pigment content, especially chlorophyll a, increased with increasing ferulic acid concentrations. The total paramylon production would also be enhanced by ferulic acid since the number of cells increased without reducing the cellular content of paramylon.